Enhancing fatty acid production in Escherichia coli by Vitreoscilla hemoglobin overexpression. Issue 2 (17th August 2016) - Liu, Di; Wan, Ni; Zhang, Fuzhong; Tang, Yinjie J.; Wu, Stephen G.
ABSTRACT: Our recent 13 C‐metabolic flux analysis ( 13 C‐MFA) study indicates that energy metabolism becomes a rate‐limiting factor for fatty acid overproduction in E. coli strains (after "Push‐Pull‐Block" based genetic modifications). To resolve this bottleneck, Vitreoscilla hemoglobin (VHb, a membrane protein facilitating O2 transport) was introduced into a fatty‐acid‐producing strain to promote oxygen supply and energy metabolism. The resulting strain, FAV50, achieved 70% percent higher fatty acid titer than the parent strain in micro‐aerobic shake tube cultures. In high cell‐density bioreactor fermentations, FAV50 achieved free fatty acids at a titer of 7.02 g/L (51% of the theoretical yield). In addition to "Push‐Pull‐Block‐Power" strategies, our experiments and flux balance analysis also revealed the fatty acid over‐producing strain is sensitive to metabolic burden and oxygen influx, and thus a careful evaluation of the cost‐benefit tradeoff with the guidance of fluxome analysis will be fundamental for the rational design of synthetic biology strains. Biotechnol. Bioeng. 2017;114: 463–467. © 2016 Wiley Periodicals, Inc. Abstract : Energy metabolism is a rate‐limiting factor for fatty acid overproduction in E. coli strains. Vitreoscilla hemoglobin overexpression promotes oxygen supply and increases free fatty acid production under micro‐aerobic conditions. The "Push‐Pull‐Block‐Power" strategy and metabolic burden analysis may offer rational design of synthetic biology strains.